Designing 3D printed ceramic lattice structures for osseointegrative implants (Transactions on Additive Manufacturing Meets Medicine, 2023)
Modern 3D printing techniques make it possible to produce implants using high-performance ceramic material. Ceramic materials such as zirconia (ZrO2) have some advantages over previously used materials such as titanium, as they possess high strength and are especially good for bone integration. To have optimal osseointegrative /osteoconductive properties it is helpful to produce a lattice structure with pores and a large surface area, rather than a bulk ceramic part, which can be done utilizing additive manufacturing. Lattice structures allow bone cells to grow well into an implant that has a hollow interior and can lead to a reduction of the high stiffness to a level similar to bone material to avoid stress shielding. The aim of this study was to investigate different types of lattices with respect to their mechanical properties (compression, tension, shear, bending). The results will help to determine the most appropriate lattice designs for future implants. Seven different graph-based lattice types, each with 80% porosity, were designed, simulated by finite element analysis, and up to 25 ZrO2 specimens were fabricated using stereolithography and thermal post-processing. The design geometries of the specimens were partly inspired by the literature, where this microarchitecture has already been investigated for osseointegrativity and osseoconductivity. In addition to regular lattice geometries a Voronoi lattice was included with an average pore size comparable to the other structures. All these specimens were tested in compression, tension, shear, and flexure to determine their Young's modulus and fracture strength. Weibull statistics were used to determine the fracture risk of each structure, depending on the applied stress. Although all the structures had the same porosity and therefore the same weight, the surface area and mechanical stability varied. The measured compression elasticity for the different structures varied in the range of 5 GPa to 26 GPa, which corresponds to the stiffness range of bone material. Since slight variations in geometry occur during fabrication, the finite element simulation does not exactly match the measurement results, but gives a good estimate (differences
Keywords: lattice; ceramic; mechanical testing; additive manufacturing; Young's modulus; breaking strength